2013
DOI: 10.1590/s1517-83822013005000003
|View full text |Cite
|
Sign up to set email alerts
|

Bio-preservation of ground beef meat by Enterococcus faecalis CECT7121

Abstract: Meat and particularly ground beef is frequently associated with Food Poisoning episodes and breeches in Food Safety. The main goal of this research was to evaluate the bactericide effect of the probiotic Enterococcus faecalis CECT7121, against different pathogens as: Escherichia coli O157:H7, Staphylococcus aureus, Clostridium perfringens and Listeria monocytogenes, inoculated in ground beef meat. Three studies were performed to evaluate the inhibition of E. faecalis CECT7121 on ground beef meat samples inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…It was revealed that the application of L. delbrueckii bacteria doesn't causes any changes in sensory characteristics of ground beef entire 10 days storage, moreover promote expanding of shelf-life due to inhibition of psychrophilic spoilage microorganisms which is in agreement with other authors [6,[24][25][26][27]. Thus, the LAB treated samples keep good quality for ten days whilst in the control sample at 7 day of storage appeared undesirable odor, greening and smooth on surface.…”
Section: Lab Inhibitory Effect On E Coli O157:h7 In Groundsupporting
confidence: 85%
“…It was revealed that the application of L. delbrueckii bacteria doesn't causes any changes in sensory characteristics of ground beef entire 10 days storage, moreover promote expanding of shelf-life due to inhibition of psychrophilic spoilage microorganisms which is in agreement with other authors [6,[24][25][26][27]. Thus, the LAB treated samples keep good quality for ten days whilst in the control sample at 7 day of storage appeared undesirable odor, greening and smooth on surface.…”
Section: Lab Inhibitory Effect On E Coli O157:h7 In Groundsupporting
confidence: 85%
“…These two species have been previously reported to be susceptible to enterococcal bacteriocins (Rivas et al 2012). It is generally recognized that the inhibitory activity of enterococcal bacteriocin encompasses Gram-positive (Szabό et al 2009) as well as food protection against pathogenic pathovars of E. coli (Sparo et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In contrary, Reham, Amin (2012) found that growth of Staphylococcus aureus in minced meat samples stored at 4°C was completely inhibited after being treated with Lactobacillus acidophilus in the 3 rd day of the experimental time. Also, Sparo et al (2013) concluded that, no Staph. aureus viable bacteria were detected at 48 h in ground beef meat post-treated with probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Berenice Arias et al (2013) mentioned that, Lactobacillus acidophilus and Bifidobacteriumhad the same antagonistic effect against Escherichia coli O157:H7. In addition, Sparo et al (2013) through a comprehensive study, found that E. coli O157:H7growth was completely inhibited and the viable cells were not detected at 72 h in ground beef samples treated with probiotics.…”
Section: Discussionmentioning
confidence: 99%